Silver nanoparticles incorporated konjac glucomannan-montmorillonite nacre-like composite films for antibacterial applications. (1st October 2018) - Zhu, Wenkun; Li, Jiwei; Lei, Jia; Li, Yi; Chen, Tao; Duan, Tao; Yao, Weitang; Zhou, Jian; Yu, Yang; Liu, Yan
Highlights: Composite film with a pearl shell layered structure. Nano silver particles conferred antibacterial ability on composite film. Montmorillonite enhanced the mechanical strength of the composite film. Abstract: Artificial nacre-like konjac glucomannan-Montmorillonite (KGM-MTM) composite films with 'brick and mortar' microstructures have been fabricated based on using KGM-MTM hybrid nanosheets as building blocks. In the designed fabrication procedure, we assembled hybrid building blocks with a thin layer of KGM coating on the MTM nanosheets to form KGM-MTM composite film via vacuum filtration. The nacre-like microstructures enhanced the light transmission performance and mechanical properties (Tensile strength: 116 MPa) of KGM-MTM composite films. Additionally, Ag nanoparticles (Ag NPs) can be incorporated into the layered structures of KGM-MTM composite films via an in situ reduced method. It was found that KGM-MTM-Ag composite films significantly suppress bacterial growth, which makes them potentially applicable as antimicrobial films in the biomedical field.